Effect of Personal Protection Equipment (PPE) and the Distance From the Eye Piece of Surgical Microscope on the Field of Vision; An Experimental Study. Issue 4 (April 2021) - Iyer, Arunachalam; Tikka, Theofano; Calder, Nicholas; Qamar, Sabih Nadeem; Chin, Andy
Abstract : Background: During the Covid-19 pandemic, otolaryngologists are at risk due to aerosol-generating procedures such as mastoidectomy and need enhanced personal protective equipment (PPE). Eye protection can interfere with the use of a microscope due to a reduction in the field of vision. We aimed to study the effect of PPE on the microsurgical field. Methods: Five surgeons measured the visual field using digital calipers at different power settings. They were done with no PPE, a surgical mask, FFP3 mask (N99), and with the addition of small goggles, large vistamax goggles, vistamax plus a face shield, and only a face shield. The measurements were repeated with rings of 5 mm increments. We also measured the "eye relief" of the microscope which is the ideal distance for maximum field of view. Results: There was no major reduction of the field with the surgical or FFP3 mask. But even simple goggles reduced the field up to 31.6% and there were progressive reductions of up to 75.7% with large goggles, 76.8% when a face shield was added, and 61.9% when only face shield was used. The distance rings more than 5 mm also affected the field of view. The eye relief of our eyepiece was found to be 15 mm. Conclusion: The current PPE eye protection is not compatible with the use of a microscope. There is scope for research into better eye protection. Mitigation strategies including barrier drapes and alternative techniques such as endoscopic surgery or use of exoscopes should also be considered.